CONCEPTUALIZING CRITICAL THINKING LEARNING TRANSFER MODEL: A QUALITATIVE APPROACH (Malaysian Journal of Learning and Instruction, 2021)
Purpose – Although there is a growing interest in Critical Thinking Learning Transfer (CTLT), detailed information regarding the transfer seems to be lacking, particularly in the Malaysian context. In addition, past studies have not focused on medical education. This raises the question: How do Malaysian medical undergraduates transfer their critical thinking learning? Thus, this study sought to explore the CTLT process among medical undergraduates in Malaysia, synthesize the CTLT model and present the types of CTLT.Methodology – A qualitative case study approach was adopted. Eight medical undergraduates were selected using purposive sampling, through two sampling strategies. Data was obtained via in-depth interviews and analysed using thematic analysis.Findings –Three types of CTLT were found, namely near transfer, far transfer, and integrated transfer. Each type of transfer was specified into components. The participants’ conceptions of the CTLT process led to the development of a model that presented the types of CTLT and provided a better understanding of the extension of occurrence of CTLT among medical undergraduates. Significance – The CTLT model adds value to the description of the CTLT process among students, especially in the context of the early clinical year medical programme. The model may also influence the future development of critical thinking pedagogies.